Facilitating communication with overweight children in dietetic settings: development and feasibility testing of an interactive e-resource (Feed-back) - Raaff, Carol Anne (2016)
Child obesity is a significant health concern and treatment typically involves referral to child weight management services (CWM). Evidence suggests that preadolescent children may benefit from greater involvement in their treatment but the younger child can find it difficult to enter treatment discussions, and being overweight can negatively affect child self-esteem and capacity to communicate. Digital technology has the potential to provide scaffolding for child consultations with dietitians by presenting information in an accessible, engaging and interactive format. This research aimed to develop a theory driven, evidence-based interactive e-resource (Feed-back) and to explore the feasibility and acceptability of using Feed-back to facilitate communication between children aged 7 to 11 years and the dietitian within child weight management appointments.